If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 13 + 5x = 3 + x + 10 Reorder the terms: 13 + -4x + 5x = 3 + x + 10 Combine like terms: -4x + 5x = 1x 13 + 1x = 3 + x + 10 Reorder the terms: 13 + 1x = 3 + 10 + x Combine like terms: 3 + 10 = 13 13 + 1x = 13 + x Add '-13' to each side of the equation. 13 + -13 + 1x = 13 + -13 + x Combine like terms: 13 + -13 = 0 0 + 1x = 13 + -13 + x 1x = 13 + -13 + x Combine like terms: 13 + -13 = 0 1x = 0 + x 1x = x Solving 1x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1x + -1x = x + -1x Combine like terms: 1x + -1x = 0 0 = x + -1x Combine like terms: x + -1x = 0 0 = 0 Simplifying 0 = 0 The solution to this equation could not be determined.
| -9+2n/9 | | 8x-2=6x+3 | | -7-(-43)=x/9 | | b=8/3(j-68) | | x/3=2x/15+8 | | y=3.08sqrt(75)+20.08 | | (13x-2)7=133 | | z/2+1=4-z/2 | | J+2/3+5j/6=4j-5/12 | | 58+(x-7)=180 | | 175m-75m+47500=50000-150m | | 3x/20-6x=1/10 | | -13+-13= | | -2(b-5)=-4 | | -4x+4y=-14 | | 5-x=12x-8 | | 7n+12=-6n | | 2(x-1)=3(x+4) | | 3(2x-1)-6=2x+3 | | (2cd^3)= | | 4[2x+4]=10x+15-2x+1 | | 2(3-4+1)=22 | | y+5=03 | | d/4-9=(-3) | | 3.625x+2=4.5 | | -x^3+2x^2+4x+72=0 | | 10+9x=-152 | | 0.1-0.02(x+2)=-0.03(3-x) | | J+2/3+5j=4j-5/12 | | 2(3i)= | | 100m+57900=61500-200m | | 5c-3+2c=46 |